Plasmid segregation and stability in bacteria - Funnell, Barbara (Henry Stewart Talks, 2008)
Mechanisms of plasmid segregation and partition reactions, Types of plasmid partition systems in bacteria, ParA partition ATPases, Structural biology of partition-site binding proteins, Chromosome dynamics
Archived at 2024/01/31